The Effect of Perceived Usefulness, Perceived Ease of Use and Security on Behaviour Intention of BRImo Application on Gen Z In the City of Padang - Ulviya Ramadhani; Fitria Ridhaningsih (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to analyze the influence of perceived usefulness, perceived ease of use, and security on the behavioral intention of the BRImo application among Gen Z in Padang City. This study employs a quantitative approach with a purposive sampling design, involving 200 respondents who are users of the BRImo app. Primary data was collected through an online questionnaire distributed to Gen Z individuals who either intend to use or have already used the BRImo app. The analytical methods applied include descriptive analysis and multiple regression analysis using SPSS software version 25. The results of the study indicate that: (1) Perceived Usefulness has a significant influence on the Behaviour Intention of the BRImo application among Gen Z in Padang City; (2) Perceived Ease of Use also has a significant influence on Behaviour Intention among Gen Z in Padang City; and (3) Security significantly contributes to the Behaviour Intention of the BRImo application among Gen Z in Padang City. These findings provide important insights for app developers in enhancing the adoption and usage of BRImo among the younger generation.